STRATEGI PENGELOLAAN PROGRAM PERMODALAN PERTANIAN UNTUK MENINGKATKAN AKSES PERMODALAN PETANI HORTIKULTURA (Kasus Program PT. Elevarm Di Kecamatan Cimaung, Kabupaten Bandung) - Azka, Khalish Muhammad; Rosmiati, Mia; Sofiatin, Sofiatin (Universitas Galuh, 2023)
The agricultural sector is still one of the biggest pillars of the economy in developing countries, one of which is Indonesia. Even so, the income of rural farmers in Indonesia is still low (an average of 1 million/month), which has an impact on low capital resources for farming so farmers need access to agricultural capital. Farmers' access to institutional sources of agricultural capital in rural areas is still not optimal and faces various obstacles, including Cimaung District, Bandung Regency, West Java. This study aims to determine the socio-economic characteristics of farmers, farmers' access to sources of capital, and loan repayment of PT Elevarm partner farmers with the ultimate goal of determining the management strategy for the agricultural capital program for PT Elevarm as an evaluative step. The method used in this research is a multiple linear regression method to determine the effect of socio-economic characteristic variables on access to farmer capital and repayment of farmer loans and the SWOT-QSPM method to design a management strategy for agricultural capital programs. The results of the analysis show that the socio-economic characteristics of the variables age, gender, and distance to sources of capital have a negative effect and the variable land size has a positive effect on access to sources of capital. The results of the analysis also show that socio-economic characteristics have no significant effect on the repayment of farmer loans. The results of the agricultural program management strategy design indicate the ST (Strength-Threat) strategy that must be prioritized in management. The details of alternative strategies based on priority order from the results of the QSPM analysis are (1) Formation of a membership scheme that is more binding with the contribution system. (2) Organizing large events for corporate branding. (3) Leasing cultivation land to form a cooperation program with farmers.